Monoclonal antibodies to crystal protein of Bacillus thuringiensis subspecies israelensis - TEMEYER; KEVIN B; PRUETT; JOHN H; HAUFLER; MAURICE (1990)
Murine hybridomas are disclosed which were constructed by fusing spleen cells from BALB/c mice immunized with soluble crystal protein from Bacillus thuringiensis subsp. israelensis (B.t.i.) to the murine myeloma cell line SP2/0-AG14. An ELISA (enzyme-linked immunosorbent assay) method for detection of antibodies specific for crystal protein of B.t.i. was modified to produce 100- to 1,000-fold increased sensitivity and was used to identify hybridomas secreting monoclonal antibody specific for the B.t.i. crystal protein. Analysis of the hybridoma culture supernatant fluid indicated production of monoclonal IgG3 antibodies, specific for the 68,000 dalton protein presumed to be the insecticidal delta-endotoxin of B.t.i.